Biodegradable silk-based products for regenerative medicine - E. I. Podbolotova; O. I. Agapova (Вестник трансплантологии и искусственных органов, 2025)
Silk is becoming one of the key materials in contemporary bioengineering and medicine due to its unique physicochemical and biological properties. This review article discusses the main components of silk, fibroin and sericin, their structure and functional characteristics, as well as their importance in the production of biocompatible and biodegradable materials. Modern methods of modifying silk to enhance its mechanical and biological properties are considered, including physical, chemical, and genetic manipulation. The use of silk in tissue engineering, development of medical implants, controlled drug delivery systems, and biosensors is given particular consideration. In conclusion, the prospects for further silk research targeted at creating innovative biomaterials for medical applications are discussed.